Effect of LuxS/AI-2-mediated quorum sensing system on bacteriocin production of Lactobacillus plantarum NMD-17 - Man, Li-Li; Xiang, Dian-Jun (Folia microbiologica, 2023)
Lactobacillus plantarum NMD-17 separated from koumiss could produce a bacteriocin named plantaricin MX against Gram-positive bacteria and Gram-negative bacteria. The bacteriocin synthesis of L. plantarum NMD-17 was remarkably induced in co-cultivation with Lactobacillus reuteri NMD-86 as the increase of cell numbers and AI-2 activity, and the expressions of luxS encoding signal AI-2 synthetase, plnB encoding histidine protein kinase, plnD encoding response regulator, and plnE and plnF encoding structural genes of bacteriocin were significantly upregulated in co-cultivation, showing that the bacteriocin synthesis of L. plantarum NMD-17 in co-cultivation may be regulated by LuxS/AI-2-mediated quorum sensing system. In order to further demonstrate the role of LuxS/AI-2-mediated quorum sensing system in the bacteriocin synthesis of L. plantarum NMD-17, plasmids pUC18 and pMD18-T simple were used as the skeleton to construct the suicide plasmids pUC18-UF-tet-DF and pMD18-T simple-plnB-tet-plnD for luxS and plnB-plnD gene deletion, respectively. luxS and plnB-plnD gene knockout mutants were successfully obtained by homologous recombination. luxS gene knockout mutant lost its AI-2 synthesis ability, suggesting that LuxS protein encoded by luxS gene is key enzyme for AI-2 synthesis. plnB-plnD gene knockout mutant lost the ability to synthesize bacteriocin against Salmonella typhimurium ATCC14028, indicating that plnB-plnD gene was a necessary gene for bacteriocin synthesis of L. plantarum NMD-17. Bacteriocin synthesis, cell numbers, and AI-2 activity of luxS or plnB-plnD gene knockout mutants in co-cultivation with L. reuteri NMD-86 were obviously lower than those of wild-type strain in co-cultivation at 6-9 h (P < 0.01). The results showed that LuxS/AI-2-mediated quorum sensing system played an important role in the bacteriocin synthesis of L. plantarum NMD-17 in co-cultivation.
Keywords: bakteriální proteiny; regulace genové exprese u bakterií; Lactobacillus plantarum; Bacterial Proteins; Gene Expression Regulation, Bacterial; lidé; Plasmids; Bacteriocins; Lactobacillus; plazmidy; Quorum Sensing; bakteriociny; quorum sensing; Humans